Systemic inflammatory index a simple marker of thrombo-inflammation and prognosis in severe COVID-19 patients - Ramesh, Jayanthy; Varghese, Johann; Reddy, S. L. Sagar; Rajesh, Moganti (International Journal of Advances in Medicine, 2021)
Background: COVID-19 pandemic has challenged the healthcare resources globally, inspiring the need for identifying simple, economical biomarkers. COVID-19 is an immune-inflammatory disorder and systemic inflammatory index (SII) derived from the peripheral blood has been proposed as a marker. Methods: Retrospective study of severe COVID-19 hospitalized patients (total N=154 including diabetic subset N=57). Data regarding hematological variables such as absolute neutrophil count (ANC), absolute lymphocyte count (ALC), platelet count along with thrombo-inflammatory proteins, D-dimer, C-reactive protein (CRP) were extracted from medical records. SII was calculated from ANC×platelets/lymphocyte count. Clinically applicable cut-offs were derived using the receiver operating characteristic curve (ROC) analysis for SII, CRP and D-dimer. Correlations between hematological parameters and D-dimer, CRP were analyzed to validate them as biomarkers of thrombo-inflammation and as predictors of clinical outcome. Results: Among 154 severe COVID-19 patients, significant association with mortality was seen with respect to ANC (p<0.001), SII (p=0.01), CRP (p=0.004) and D-dimer (p=0.001). In the total COHORT, based on ROC curve, applicable cut-off for outcome prediction were for SII 14.85×105 (area under curve (AUC)-0.691, sensitivity-67%, specificity-64%,odds ratio (OR)-3.44), CRP 19.7 mg/l (AUC-0.718, OR-5.71), D-dimer 0.285 mcg/ml (AUC-0.773, OR-6.94) respectively. In the diabetic subset, the cut-offs for SII 14.85×105 (AUC-0.68, sensitivity-80%, specificity-54%, OR-4.7), CRP 52.5 mg/l (AUC-0.723, OR-5.36) and D-dimer 0.285 mcg/ml (AUC-0.771, OR-11.3) respectively. Conclusions: Clinically applicable thresholds for SII serve as reliable biomarkers of thrombo-inflammation and prognosis in severe COVID-19 patients. Diabetic patients with similar thresholds had higher risk and prediction for mortality. In the resource constrained health care settings, who might not afford D-dimer, SII may serve as an economical bio-maker.